The Role of Ustadzah in Improving the Akhlakul Karimah of Students Class 5 at Ibtida'iyah Madrasah Islamiyah Darul Falah - Mufti, Raviqha; Irhamuddin, Irhamuddin; Ehwanudin, Ehwanudin (International Journal on Advanced Science, Education, and Religion, 2025)
Akhlakul Karimah is one of the fundamental aspects of Islamic education that must be instilled from an early age, in the world of education, especially in the madrasa environment. In this context, the ustadzah has a very important role in guiding, directing and instilling moral values in the students. The role of the ustadzah in improving the morals of the students is very much needed in the Islamic madrasah "Darul Falah" Central Lampung because it aims to realize the vision and mission of the madrasah. Madrasah "Darul Falah" is a school institution within the scope of the Islamic Boarding School "Darul Ulum". This article aims to analyze the role of Ustadzah in improving the Akhlakul Karimah of grade 5 students at Madrasah Islamiyah "Darul Falah". The methods used are case studies and field studies. The research sample was 4 teachers and several students. In this research, researchers used several data collection tools, namely through observation, interviews and documentation. This research uses triangulation of sources and methodology to ensure the authenticity of the data. The results of the research show that there are efforts made by Ustadzah to improve the morals of class 5 students, the students become more orderly in carrying out activities, can apply positive things and can avoid negative things. Not only can you get used to good things, class 5 students can be a good example for their juniors. From these efforts, the quality of the morals of class 5 students.